Fabrication of NiO/SnO2 heterojunction based photocatalyst for efficient sunlight degradation of organic dyes - Imran Shakir; Sajjad Haider; Philips O. Agboola; Najeeb Faud Al-Khalli (Journal of Taibah University for Science, 2021)
A new composite oxide (NiO/SnO2) photocatalyst was synthesized by simple co-precipitation route. The structural elucidation of composite oxide photocatalyst was carried out via X-rays diffraction (XRD) technique. The morphology was determined by scanning electron microscopy (SEM). The Fourier transform infra-red (FTIR) and UV–visible spectroscopic techniques revealed the spectral and optical features. XRD analysis confirmed the formation of binary metal oxide nanocomposite comprising NiO in cubic and SnO2 in the tetragonal crystalline phase. The crystallite size for NiO/SnO2 calculated from XRD was < 15 nm. The spectroscopic studies also supported the XRD data. The morphological study of NiO/SnO2 revealed the formation of relatively small rounded nanoparticles. The solar light driven photocatalytic degradation study showed about 54% degradation of methylene blue and 34% degradation of Congo red and the value of rate constant for NiO/SnO2 was found to be 0.0059 min−1. The mechanism of degradation of dyes was also explored and discussed.